Review on Digital Transformation Policy of Directorate Generale of Taxes - Riyanto Riyanto; Amalia Dewi Clarashinta (Yayasan Ilomata, 2021)
The Covid-19 pandemic caused a reduction in face-to-face interaction between people. Changes in social interaction from offline to online need supporting facilities, both internet networks, computers, gadgets, and other items. The Directorate General of Taxes (DGT) as the government agency that collects state revenues from taxes, is constantly transforming towards improving public services, especially to taxpayers. Many applications of e-tax systems that have been developed by DGT are Nadine, e-faktur, e-billing, e-filling, and DJP Online. This electronic reporting has influenced the increase of Annual Tax Return reporting for the last three years.